The Role of Community Health Nursing in Insulin Initiation for Type 2 Diabetes Patients: A Literature Review: Insulin Initiation for Type 2 Diabetes - Saltar, Laode (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: Insulin therapy is essential for managing type 2 diabetes in patients who do not achieve adequate glycemic control with oral medications. Despite its benefits, initiating insulin therapy presents numerous challenges due to psychological, physical, and systemic barriers. This study examines the critical role of community health nurses in facilitating the initiation and management of insulin therapy, addressing patient and healthcare provider barriers, and improving clinical outcomes. Methods: A comprehensive review of existing literature was conducted, focusing on the impact of community health nurses on diabetes management, particularly in insulin initiation and adherence. Results: : Community health nurses play a pivotal role in overcoming barriers to insulin therapy. They provide essential patient education, psychosocial support, and practical training in insulin administration. These efforts lead to improved glycemic control, higher rates of insulin adherence, and better patient satisfaction. Additionally, community health nurses facilitate collaborative care models, integrating with primary care teams to provide continuous and coordinated care. The involvement of community health nurses in diabetes management addresses both patient-related and systemic barriers. Their holistic approach includes personalized patient education, emotional support, and care coordination, significantly enhancing patient adherence and clinical outcomes. Conclusions: Community health nurses are integral to the successful initiation and management of insulin therapy in type 2 diabetes. Future research should focus on developing standardized training programs for community health nurses and exploring innovative care models that leverage their unique skills. Policy support is essential to recognize and expand the role of community health nurses in diabetes care.